Aligned hollow coaxial microfibers based substrate for in vitro cell culture - Li, Bo Yuan (2018)
Nowadays, tissue engineering has a wide application in many fields, ranging from toxicology, medical devices, tissue replacement, repair and regeneration. Currently tissue engineering mainly focuses on development of tissue and organ substitutes, where experimental parameters of various fabrication techniques are controlled to get a three-dimensional (3D) cellular construct which has comparable properties to native tissue. A major goal of tissue engineering is to generate extracellular matrix (ECM) analogues which are called scaffolds, embed cells into them, and then adjust the environment in a manner suitable for cell attachment and growth. Several techniques are used at present to fabricate these scaffolds depending on the type of application i.e. in vivo or in vitro conditions. In this study, aligned coaxial microfibers with porous surface were fabricated as a substrate for in vitro cell culture based on modifying the traditional electrospinning technique by using a core-shell spinneret and a rotating mandrel. Using this method, aligned and porous coaxial microfibers with suitable diameter and morphology were produced with PC12 cells encapsulated inside, therefore achieving a direct fabrication of cell-scaffold structure. Poly-ε-caprolactone (PCL) and poly-vinylalcohol (PVA) are used as shell and core materials respectively. The core was removed subsequently during cell culture to create a hollow structure; the cells were observed to survive after the electrospinning process, attach to the inside surface of the hollow fiber, and grow and proliferate for the duration of the culture process. The results prove the feasibility of this substrate for long term directional cell culture and highlights its potential for cell differentiation and aligned cell cultivation, for example in the case of neuronal and muscle tissues.